2014
DOI: 10.1182/blood-2014-05-573055
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant long-acting glycoPEGylated factor IX in hemophilia B: a multinational randomized phase 3 trial

Abstract: Key Points Nonacog beta pegol, a recombinant glycoPEGylated FIX with extended half-life, was developed to improve care for patients with hemophilia B. Weekly prophylaxis with nonacog beta pegol was well tolerated and was associated with low bleeding rates and an improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
266
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(278 citation statements)
references
References 21 publications
11
266
0
1
Order By: Relevance
“…The patient population was geographically diverse and included patients from North America, Europe, Asia, and the Middle East (Table 1). More than half of the patients in both groups 1 and 2 reported chronic hemarthrosis or a target joint at the start of the study (see footnote of Table 1 for details 20 ). Group 2 patients (on-demand prior to study entry) reported a higher median nontrauma-induced bleeding rate than group 1 patients during the 12 months prior to study entry (21.0 vs 1.0).…”
Section: Patient Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…The patient population was geographically diverse and included patients from North America, Europe, Asia, and the Middle East (Table 1). More than half of the patients in both groups 1 and 2 reported chronic hemarthrosis or a target joint at the start of the study (see footnote of Table 1 for details 20 ). Group 2 patients (on-demand prior to study entry) reported a higher median nontrauma-induced bleeding rate than group 1 patients during the 12 months prior to study entry (21.0 vs 1.0).…”
Section: Patient Characteristicsmentioning
confidence: 96%
“…20 ||Bleeding episodes in the 12 months prior to study entry. {Nontrauma defined as spontaneous and unknown cause bleeding episodes.…”
Section: Safetymentioning
confidence: 99%
“…The conjugation of a 40-kDa branched polyethylene glycol (PEG) molecule to rFIX increases the half-life and enables once weekly prophylactic dosing instead of twice weekly dosing with unmodified rFIX (Collins et al 2014). Human coagulation factors are immunogenic in animals, precluding the possibility to conduct chronic toxicity studies (European Medicines Agency 2004b, 2005Ivens and Arora 2013;Kirschbaum and U.S. Food and Drug Administration 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All approaches described above achieve only moderate increases of half-lives (1.5-to 2-fold compared to unmodified FVIII) [23]. This is in contrast to FIX where it was possible to increase the mean half-life 4-to 6-fold by different forms of bioengineering [24][25][26]. and pharmacokinetics in two pivotal phase 3 studies [27,28].…”
Section: Limitations Of Prolonging Half-life Of Fviiimentioning
confidence: 98%
“…Nonacog beta pegol (N9-GP; Refixia ® ) is a recombinant FIX product (Chinese hamster ovary cell line) linked to 40 kDa PEG moiety (attached to the FIX activation peptide) [26]. In a phase 3 study, 74 PTPs > 12 years with severe to moderately severe hemophilia B were randomized to either 10 (n = 30) or 40 IU/kg (n = 29) once-weekly prophylaxis or on demand treatment (n = 15) [26].…”
Section: Pegylated Fixmentioning
confidence: 99%